Pengaruh Viral Marketing, Celebrity Endorsment dan Brand Image Tehadap Keputusan Pembelian Reksadana pada Aplikasi Bibit - I Made Chandra Mandira; I Putu Gede Wahyu Putra Arnata (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
Bibit is an online mutual fund provider application where this application acts as an agent who helps sell mutual fund products from investment managers. Vial Marketing, Celebrity Endorsement, and Brand image were selected for the decision to purchase mutual funds in the Seeds application in Kuta. The purpose of this study was to determine the effect of Viral Marketing, Celebrity Endorsement, and Brand Image together on mutual fund purchasing decisions on the Bibit application in Kuta. The sample used in this study was Nonprobability Sampling, namely purposive sampling with a total sample of 102. The method used in this study was quantitative using the Classical Assumption Test, Multiple Linear Regression Analysis and Hypothesis Testing. The results of the study found that the Viral Marketing, Celebrity Endorsement, and Brand Image variables had a positive and significant effect on purchasing decisions. The results of the T test in this study, namely Viral Marketing has a significant value of 0.002, Celebrity Endorsement has a significant value of 0.020, and Brand Image has a significant value of 0.000. The results of the F test in this study have a significant value of 0.000 less than 0.05, which means that simultaneously Viral Marketing, Celebrity Endorsement, and Brand Image have a positive and significant effect on Purchasing Decisions. This research is expected to be able to provide information to the management of Bibit regarding Viral Marketing, Celebrity Endorsements, and Brand Image for purchasing decisions which can be useful for related management so that they can develop appropriate strategies in future consumer purchase intention decisions.